Numerical modeling of reservoir sedimentation and flushing processes - Ahn, Jungkyu, author; Yang, Chih Ted, advisor; Julien, Pierre Y., committee member; Thornton, Christopher I., committee member; Wohl, Ellen E., committee member (Colorado State University. Libraries, 2011)
As rivers flow into reservoirs, part of the transported sediment will be deposited. Sedimentation in the reservoir may significantly reduce reservoir storage capacity. Reservoir capacity can be recovered by removing deposited sediment by dredging or flushing. Generally speaking, the latter is preferable to the former. An accurate estimation sedimentation volume and its removal are required for the development of a long term operation plan in the design stage. One-dimensional, 1D, models are more suitable for a long term simulation of channel cross section change of a long study reach than two or three dimensional models. A 1D model, GSTARS3, was considered, because this study focuses on sedimentation and flushing in the entire reservoir over several years and GSTARS3 can predict channel geometry in a semi-two dimensional manner by using the stream tube concept. However, like all 1D numerical models, GSTARS3 is based on some simplified assumptions. One of the major assumptions made for GSTARS3 is steady or quasi-steady flow condition, which is valid for most reservoir operation. If there is no significant flow change in a reservoir, such as rapid water surface drop during flushing, steady model can be applied. However, unsteady effect due to the flushing may not be ignored and should be considered for the numerical modeling of flushing processes. Not only flow characteristics but also properties of bed materials in reservoir regime may be different from those in a river regime. Both reservoir and river regimes should be considered for a drawdown flushing study. Flow in the upper part of a reservoir may become river flow during a drawdown flushing operation. A new model, GSTARS4 (Yang and Ahn, 2011) was developed for reservoir sedimentation and flushing simulations in this study. It has the capabilities of simulating unsteady flow and coexistence of river and reservoir regimes in the study area. GSTARS4 was applied to the Xiaolangdi Reservoir, located on the main stream of the Yellow River. The sediment concentration in the reservoir is very high, 10 ~ 100 kg/m3 for common operation and 100 ~ 300 kg/m3 for flushing operation, with very fine materials about 20 ~ 70 % of clay. Stability criteria for computing sediment transport and channel geometric changes by using GSTARS4 model was derived and verified for the Xiaolangdi Reservoir sedimentation and flushing computations. Han's (1980) non-equilibrium sediment transport equation and the modified unit stream power equation for hyper-concentrated sediment flows by Yang et al. (1996) were used. Both unsteady and quasi-steady simulations were conducted for 3.5 years with calibrated site-specific coefficients of the Xiaolangdi Reservoir. The computed thalweg elevation, channel cross section, bed material size, volume of reservoir sedimentation, and gradation of flushed sediments were compared with the measured results. The unsteady computation results are closer to the measurements than those of the steady flow simulation results.
Keywords: flushing; GSTARS; modeling; reservoir; sedimentation; sediment